Effect of varying silica-limestone sand fines on the physical-mechanical performance of concrete (Fracture and Structural Integrity, 2021)
The use of crushed limestone sand in the concrete industry will be quite possible and imperative for environmental reasons. Many researchers around the world have found that concrete based on 50% substitution of river sand by limestone sand gives better physico-mechanical characteristics. The main objective of this investigation is to search for an optimal percentage of silica-limestone fines resulting from the substitution of half in quantity of alluvial sand by crushed limestone sand in ordinary concrete. The proportions of fines that were tested in this work are 6%, 8%, 10%, 12% and 14%.The obtained results revealed that concrete based on silica-limestone sand and containing 14% of the same type of fines strongly improves the different mechanical strengths and participates in the reduction of 10% and 13%, of the coefficient of capillary absorption and of the porosity accessible to water, respectively, compared to the control concrete. In addition, good statistical relationships between the studied parameters were also found
Keywords: Silica-limestone sand; silica-limestone sand fines; Concrete; physical-mechanical characteristics